Weight gain in pregnancy. (18th April 2012) - Lam, S; Kindinger, L; Phelan, L
Abstract : Assessment of weight gain during pregnancy is not standard practice in antenatal care in the UK. Recommendations on weight gain vary from 7-15kg but there is no national evidence based guidance. The American Institute of Medicine recommendations are tailored to BMI, whereby obese women BMI>30kg/m2 should aim for <7kg weight gain, and those with normal BMI 19.8-25.9 should aim to gain 11.5-16kg. The aim of this study is to look at the effect of weight gain in pregnancy. Methods: We conducted a prospective cohort study at St Mary's Hospital, London, looking at 143 term women admitted to labour ward from July to October 2011. Weight gain during pregnancy was calculated by subtracting booking weight from weight pre-delivery. Multiple gestation, stillbirths and planned caesarean sections were excluded. Results: 62.4% gained the recommended weight (7-16kg) during pregnancy, whilst 28.6% gained more than recommended. In those with excess weight gain (regardless of BMI) there was an increased rate of pre-eclampsia (14.6% v 7.8%), need for post dates IOL (19.4% v 13.5%) and macrosomia (17% v 7%). In those who were clinically obese, weight gain >7kg was associated with an increased rate of gestational diabetes (30.7% v 20%) and need for post dates IOL (19.2% v 0%). Conclusions: These findings provide further evidence of the negative effects of excessive weight gain during pregnancy, especially in those already clinically obese. We suggest that current UK antenatal practice should include regular assessment of weight, so that excessive gain can be avoided and optimal pregnancy outcomes achieved.